Culture and institutional agency: difference in judgments of economic behavior and organizational responsibilities. Issue 2 (10th January 2014) - Lu, Xiaowei; Yao, Xiang; Cochran, Christopher; Peng, Kaiping
Abstract The current research tested the concept of institutional agency (IA) and its implications for laypeople's attribution patterns related to economic behaviors and organizational responsibilities. The term "institutional agency" refers to a set of lay theories about whether or not an organization can have personhood and related mental properties, such as wishes, desires, intents, and responsibility. Through three cross‐cultural studies, we found that people do form certain beliefs about IA which are similar to the legal discourse of institutional responsibility. However, there are significant cultural differences in views of IA, and the concept is more mentally salient for Americans than for Chinese. In Study 1, we distinguished institutional from group agency by showing the cultural differences on attributions in the scenario with "individual vs. group agency" and the scenario with "individual vs. institutional agency." In Study 2, we again demonstrated the stronger salience of IA for Americans than for Chinese by including the individual, group, and institutional agencies together in one scenario. In Study 3, we further demonstrated that the concept of IA is more salient for Americans by presenting three different agents in separate scenarios. The practical implications of these cultural differences for cross‐cultural understanding and the psychological effects of economic globalization are discussed.